2021
DOI: 10.1038/s42003-021-01736-8
|View full text |Cite
|
Sign up to set email alerts
|

Human ACE2 peptide-mimics block SARS-CoV-2 pulmonary cells infection

Abstract: In light of the recent accumulated knowledge on SARS-CoV-2 and its mode of human cells invasion, the binding of viral spike glycoprotein to human Angiotensin Converting Enzyme 2 (hACE2) receptor plays a central role in cell entry. We designed a series of peptides mimicking the N-terminal helix of hACE2 protein which contains most of the contacting residues at the binding site, exhibiting a high helical folding propensity in aqueous solution. Our best peptide-mimics are able to block SARS-CoV-2 human pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 35 publications
4
107
1
1
Order By: Relevance
“…In addition to designing RBD blockers that directly disrupt the binding between ACE2 and S protein, another approach is to identify the allosteric binding site and discover allosteric modulators, such as toremifene, to indirectly destabilize the binding between two proteins [ 43 ]. Recently, many advances have been made in the design of vaccine epitopes [ 44 , 45 ], monoclonal antibodies [ 46 , 47 ], and peptides [ 48 ] that target the S protein. Small molecular blockers that also bind to the epitopes of the spike are promising for COIVD-19 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to designing RBD blockers that directly disrupt the binding between ACE2 and S protein, another approach is to identify the allosteric binding site and discover allosteric modulators, such as toremifene, to indirectly destabilize the binding between two proteins [ 43 ]. Recently, many advances have been made in the design of vaccine epitopes [ 44 , 45 ], monoclonal antibodies [ 46 , 47 ], and peptides [ 48 ] that target the S protein. Small molecular blockers that also bind to the epitopes of the spike are promising for COIVD-19 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, further engineering was conducted by fusing ACE2 to the Fc region of the human immunoglobulin IgG1, in order to increase its plasma stability 93 , 94 . Alternatively, the N-terminal helix of ACE2 which contains most of the contacting residues at the binding site was mimicked, and the designed peptides exhibit high anti-SARS-CoV-2 activity in vitro 95 , 96 , 97 . Vice versa , a SARS-CoV-2 RBD-derived hexapeptide YKYRYL has also been proposed to possess inhibitory effect against virus entry by interfering with RBD–ACE2 interaction 98 .…”
Section: Antiviral Therapies Against Sars-cov-2 Cell Entrymentioning
confidence: 99%
“…One of their most promising peptide-mimics (P10) blocked SARS-CoV-2 human pulmonary cell infection with an IC 50 of 42 nM and 0.03 nM binding affinity ( K d ), as assessed by biolayer interferometry. 36 A recent publication also reported that four stapled peptides show antiviral activity in HT1080/ACE2 cells (IC 50 of 1.9 to 4.1 μM) and A549/ACE2 (IC 50 of 2.2 to 2.8 μM). 37 The most promising of these peptides binds SARS-CoV-2 S-RBD with a K d of 2.2 μM, as determined by SPR.…”
Section: Introductionmentioning
confidence: 94%